ONCO-HYPERTENSION – A NEW CLINICAL ENTITY IN MODERN MEDICINE - Petrović, Jelena; Radomirović, Marija; Petrović Đorđević, Ivana (Srpski medicinski časopis Lekarske komore, 2025)
Cardiovascular and oncological diseases represent an inevitable part of everyday medical practice at all levels of health care. Apart from common risk factors, these diseases are associated in other ways, and the potential cardiotoxicity of antineoplastic drugs is particularly significant. One of the frequent forms of cardiotoxicity is hypertension. Considering that it can manifest at any time during antineoplastic therapy and also after the completion of specific oncological treatment, onco-hypertension is a clinical entity that should always be kept in mind when caring for oncology patients. Regular arterial blood pressure checks in this population are necessary to ensure timely recognition and treatment of onco-hypertension and to carry out oncological treatment safely. Although the guidelines for the treatment of onco-hypertension are similar to the general recommendations for hypertension, some specificities primarily concern the choice of antihypertensive drugs and exceptions to target arterial blood pressure values depending on the stage of the oncological disease and its prognosis. It is crucial to recognize the time to stop cardiotoxic antineoplastic therapy or reduce the dose of the antineoplastic drug to avoid life-threatening cardiovascular complications. Numerous additional factors encountered in oncology patients, such as comorbidities, the presence of pain or other administered drugs, significantly contribute to the complexity of onco-hypertension. Given that this is a very sensitive population exposed to a specific type of psychological stress, the possibility of the "white coat effect" as well as masked hypertension should also be considered.
Keywords: hypertension; malignant diseases; cardiotoxicity